Two new species of Mauesia (Cerambycidae, Lamiinae, Mauesini) and key to the species of the genera - Moysés, Eleandro; Galileo, Maria Helena M. (Papéis Avulsos de Zoologia, 2009)
Mauesia simplicis sp. nov. from Brazil (Mato Grosso) and M. panamensis sp. nov. from Panama are described. A key to the species of Mauesia Lane, 1956 is added.